Work Safety and the Duration of Munition Testing - Henryk TERENOWSKI; Bogdan KRYSIŃSKI (Problemy Mechatroniki, 2017)
This paper presents the aspects of work safety and the standardization of time (duration) that relate to the diagnostic testing of munitions. This paper identifies the sources of hazards during munition disassembly, caused by the physical and chemical processes occurring during the years of service, and the hazards of non-conformities with the standard processing procedures used during the manufacture of the munitions. Munitions, given their intended use, are not usually designed for disassembly. With the manufacturing processes of munitions being monitored at every stage, and the application of proper grades or quality of the materials and components, munitions may retain their combat performance for a very long time following the expiry of their original warranty period. The extended shelf life of munitions (past the original warranty period/shelf life) can be determined with certain tests. The tests, however, require tampering with the internal structure of a munition by disassembling the munition into its component parts in order to allow assessment of the current technical condition and to project the technical fitness for extended service. Disassembly activities are hazardous and require the prior preparation of safe processes, workstations, procedures, and a comprehensive health and safety assurance system. Health and safety assurance in munition testing requires high capital expenditure to acquire sufficient engineering facilities and proper monitoring of all the disassembly activities attempted on munitions. Operator safety has the highest priority in munition disassembly; it is then pointless to regulate the time required for completing the individual disassembly operations.